Empowerment of Anemic Pregnant Women through the Provision of Iron Tablets and Ambon Bananas to Increase Hemoglobin Levels in Mondokan, Tuban Regency - Purnama Sari, Dwi Kurnia; qoyimah, ilmiatus; Nur Cholila (ABDIMASNU: Jurnal Pengabdian kepada Masyarakat, 2024)
Anemia in pregnant women is a significant public health issue, especially in rural areas like Mondokan, Tuban Regency, where access to quality healthcare and nutrition may be limited. This community service program aimed to improve hemoglobin levels in anemic pregnant women through the combination of iron tablets (Fe) and Ambon bananas, a locally available food rich in iron, potassium, and vitamin C. The program involved socialization, nutritional education, and the regular provision of iron supplements and Ambon bananas to pregnant women in the third trimester. Hemoglobin levels were measured before and after the intervention to assess the impact. Results showed a significant increase in hemoglobin levels, with 80% of participants showing improvements, averaging an increase of 1.5 g/dL. In addition, knowledge of anemia and nutrition improved markedly among participants, and the community’s engagement was high, with over 85% of women attending group support sessions. The use of Ambon bananas also contributed to local economic development, as it promoted the use of locally sourced agricultural products. This program demonstrates the potential for combining local resources and nutritional interventions to address anemia, with positive health outcomes for both pregnant women and the broader community. The findings suggest that this approach can be replicated in other regions facing similar challenges.